INFLUENCE OF LEPTIN GENOTYPES ON MILK FAT AND PROTEIN CONTENT OF CROSSBRED HOLSTEIN FRIESIAN X LAI SIND COWS - N. T. Ngu; L. T. B. Quynh; N. V. Hon; N. T. H. Nhan; D. V. A. Khoa; L. T. Hung; N. H. Xuan (Journal of Animal and Plant Sciences, 2015)
The aim of this study was to investigate leptin (LEP) gene polymorphisms in crossbred Holstein Friesian (HF) x Lai Sind cattle and their effects on milk yield and milk quality traits. Milk yield was recorded for lactation period of 305 days. Milk fat and protein were estimated using the Milko Tester machine. DNA extracted from blood samples (n=206) was amplified by PCR technique followed by sequencing for single nucleotide polymorphism (SNP) identification. Applied genotyping for the two SNPs (g.C1180T and g.C2059T) was done by PCR-RFLP method with the presence of Kpn2I and Sau3AI restriction enzymes, respectively. At the LEP/Kpn2I locus, cows of CT genotype accounted for the highest proportion (78%) whereas at the second SNP, the frequency of CC dominated (63%). In the association analysis, the LEP/Kpn2I polymorphism did not affect 305-day milk yield, but showed significant influence on milk quality traits, of which cows with CT genotype had higher protein (3.67%) and fat (3.99%) content thanones with CC and TT. The other locus (LEP/Sau3AI) was not associated with any traits analyzed. In conclusion, the g.C1180T SNP could be included in marker assisted selection of crossbred HF cows for improving protein and fat percentages.
Keywords: Cow; leptin gene polymorphism; milk quality trait